PENGARUH JUMLAH PRODUKSI PALA, KURS DAN INFLASI TERHADAP EKSPOR PALA DI INDONESIA - Nasrudin Nasrudin; Saharuddin Saharuddin; Hijri Juliansyah; Murtala Murtala (Jurnal Ekonomi Pertanian Unimal, 2023)
This study aims to analyze "The Effect of Nutmeg Production Amount, Exchange Rate and Inflation on Nutmeg Exports in Indonesia" The data used in this study is secondary data from 2005-2021 obtained from the Ministry of Agriculture and the Indonesian Central Statistics Agency, The data analysis method used in this study is Multiple Linear Analysis with the help of Eviews software, The results of the study show that partially variable Amount of Nutmeg Production does not have a significant effect on Nutmeg Exports in Indonesia, Partial testing of exchange rate variables has a significant effect on Nutmeg Exports in Indonesia and partially variables inflationary affects nutmeg exports in Indonesia and simultaneously variables of Nutmeg Production Amount, Exchange Rate and Inflation affect Nutmeg Exports in Indonesia.